Effect of topical application of monocerin on surgical wounds in murine model - Anwar, Usama Bilal (2020)
In some cases, the wound healing process demands treatment for a long time, especially in complex situation such as skin burn with severe degree that requires tissue remodeling without scars or keloids on the patient’s skin. Microorganism’s secondary metabolites are being explored as a new source of molecules that could be applied on pharmaceutical area for several purposes and previous studies showed that the secondary metabolite monocerin obtained from the fungus Exserohilum rostratum induces proliferation in human umbilical vein endothelial cells (HUVECs) and in normal human fibroblasts (FN1). In this study, the monocerin compound was obtained from the culture of the fungus E. rostratum and after purification by high performance liquid chromatography (HPLC), it was incorporated into a cream formulation at concentrations of 0.0006 and 0.005%. The effect of the formulations was evaluated on surgical wounds induced on the dorsal part of male Balb/c mice, and as control groups animals received no treatment (Untreated), or were treated with the commercial Kollagenase ointment plus chloramphenicol (collagenase 0.6 U / g + chloramphenicol 0.01 g / g, Cristália), or with the vehicle of the cream formulation. The animals were treated for 1, 3, 7 and 14 days and the wound size was measured daily with paquimeter and X-ray analysis. At the end of the treatments, the animal’s blood was collected for hematological and cytokine / chemokine analysis (IL-1β, IL-6, IL-10, TNF-α, TGF-β, FGF-2, VEGF). The wounded tissue was collected for morphological analysis hydroxyproline, histological (hematoxylin & eosin, masson trichrome and picrosirius red staining), scanning electron microscopy (SEM), and immunohistochemistry (MMP-3, MMP-9, TIMP-2, VEGF). Together with the hematological, cytokine/chemokine, SEM and Immunohistochemistry parameters, the results indicate that the treatment with monocerin was able to induce wound healing with tissue regeneration and intense collagen formation. The treatment was effective and no toxicity was observed on the animals; the wound healing process was effective without scar on the regenerated skin.